The influence of power sense on teenagers’ cooperation affection: The moderating effect of age - Zhang, Lei; Zheng, Qiuqiang; Syed Abdulla, Syed Mohamad; Li , Feifei (International Theory and Practice in Humanities and Social Sciences, 2025)
Cooperation affection is a manifestation that can reflect an individual’s emotional tendency (positive or negative) towards cooperation. Some research results show that power reduces cooperation; however, other research results show that power might increase cooperation. To understand the contradictory relationship between power and cooperation, the current study explored the influence of power sense on teenagers’ cooperative emotion (cooperation affection) among different ages (including middle school students, high school students, and university students) and found that: there was a significant decline in the cooperation affection among teenagers as they aged and gender had a marginally significant impact on teenagers’ cooperation affection; power positively predicts cooperation affection; age moderates the effect of power on the cooperation affection, which meant the influence of power sense on old teenagers’ cooperation affection was more significant.